Balancing work and family: A sociological analysis of women in raral and urban areas of Sikkim - Anada Inbanathan; Gayatri Pradhan (Bengaluru, 2016)
Balancing work and family domain has become a growing concern for every individual over the years particularly for working mothers. Thus, this study aimed at exploring the various issues encountered by women working in paid employment within the rural a
Keywords: Sikkim; Women employment; Working women